THE EFFECTIVENESS OF THE TREATMENT OF PSORIATIC ARTHRITIS - Eshmuratov Sardor Eldorovich; Uralov Rustam Sherbekovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT Goal. To evaluate the efficacy and tolerability of leflunomide, administered at a dose of 100 mg/ day for 3 days and 20 mg / day for 6 months, in patients with an active form of psoriatic arthritis (PA). Materials and methods. An open, uncontrolled study was conducted. 15 patients aged 37 to 60 years were examined, the duration of arthritis averaged 7.4 years. Leflunomide was prescribed at 100 mg / day for the first 3 days, and then 20 mg / day for 6 months. The dynamics of the number of painful and swollen joints, the severity of pain and the activity of the disease were evaluated on a visual analog scale, The Likert scale is both in the opinion of the doctor and the patient himself. Results. Against the background of leflunomide treatment, there was a significant decrease in the number of painful and swollen joints by 54.3 and 65.7%, respectively. The high efficacy of leflunomide according to the PsARC (Psoriatic Arthritis Response Criteria) and ACR 50 (American College of Rheumatology) criteria was noted in 86.7% of cases, which makes it possible to recommend it to patients with a polyarticular form of the disease. The tolerability of leflunomide was assessed as satisfactory. In 3 patients, therapy was canceled due to the development of leukopenia and urticaria. Conclusion. High efficacy of leflunomide has been demonstrated in patients with polyarticular PA.